Research in the Social Scientific Study of Religion, Volume 29 - Village, Andrew; Hood, Ralph W. (Research in the Social Scientific Study of Religion, 2018)
The general papers in Research in the Social Scientific Study of Religion, Volume 29 cover a range of topics including psychological type, prayer, nature and well-being, psychobiography, coping with addiction, and the role of place in spirituality. The first special section on congregational studies draws on a range of large datasets from the National Church Life Surveys in Australia. Papers examine the factors that predict individual sense of belonging in Catholic parishes as well as congregational-level aspects of vitality, collective confidence, and innovativeness. The second special section examines the Ideological Surround Model and how it can help to better understand expressions of faith related to psychological constructs such as mindfulness, fundamentalism, and the 'Dark Triad' of Machiavellianism, Narcissism, and Psychopathy.